1999
DOI: 10.1111/j.1572-0241.1999.01553.x
|View full text |Cite
|
Sign up to set email alerts
|

High Grade, Synchronous Colon Cancers After Renal Transplantation: Were Immunosuppressive Drugs to Blame?

Abstract: Recipients of renal transplants are known to have an increased incidence of cancer, which is believed to be related to the use of immunosuppressive drugs used to prevent rejection. Although the risks of lymphoma and Kaposi's sarcoma are clearly increased in this setting, the association with colon cancer is controversial. We report a 44-yr-old woman, 20 yr post-renal transplant, and with no family history of colorectal cancer or polyps, who was found to have synchronous, poorly differentiated colon cancers ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…[7][8][9] The Israel Penn database of the Cincinnati Tumor registry reported 386 cases of CRC in 10,667 transplant recipients. 3,10 This prevalence of 3.6 percent approximates the 3 to 5 percent reported for the general population. Other groups noted that patients with primary sclerosing cholangitis and ulcerative colitis undergoing orthotopic liver transplantation had a fourfold increase in the development of high-grade dysplasia and invasive cancer within months of their transplants.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…[7][8][9] The Israel Penn database of the Cincinnati Tumor registry reported 386 cases of CRC in 10,667 transplant recipients. 3,10 This prevalence of 3.6 percent approximates the 3 to 5 percent reported for the general population. Other groups noted that patients with primary sclerosing cholangitis and ulcerative colitis undergoing orthotopic liver transplantation had a fourfold increase in the development of high-grade dysplasia and invasive cancer within months of their transplants.…”
mentioning
confidence: 69%
“…The proposed mechanisms by which these drugs increase the risk of neoplasia include impairment of the immune surveillance of the patient, increased susceptibility of immunocompromised individuals to potentially oncogenic viral agents (e.g., Epstein-Barr virus), chronic stimulation of the lymphoreticular system related to the presence of foreign allograft antigens, and direct neoplastic actions of the immunosuppressive drugs. 3 In the ensuing 30 years since these initial postulations, there have been reports in the literature concerning the association between prolonged posttransplant immunosuppression and an increased incidence of malignancy.…”
mentioning
confidence: 98%
“…[8][9][10] Combined, these reports only represent a total of five patients, and the authors did not compare their data to the general population. In our large series of CRC in post-TXP patients (n = 150), we demonstrated that CRC are diagnosed on average 12 years earlier than patients in the NCI SEER database.…”
Section: Discussionmentioning
confidence: 99%
“…Early reports from this database did not specifically address colorectal cancer incidence, although 386 cases of colorectal cancer were identified among 10,667 transplant recipients. 5,19 As this database is comprised exclusively of transplant recipients with malignancy, a true cancer incidence is difficult to calculate. Because the University of Wisconsin transplant database is prospective for transplant recipients overall, a more reliable estimate of the incidence in this population is possible.…”
Section: Discussionmentioning
confidence: 99%